2010
DOI: 10.1016/j.socscimed.2010.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Structural forces and the production of TB-related stigma among Haitians in two contexts

Abstract: In recent years renewed interest in health-related stigma has underscored the importance of better understanding the structural underpinnings of stigma processes. This study investigated the influence of sociocultural context on perceived components of tuberculosis-related stigma in non-affected persons by comparing Haitians living in South Florida, USA, with Haitians residing in Léogane Commune, Haiti. Using the methods of cultural epidemiology, a two-phase study based on fieldwork between 2004–07 collected e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
1
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 28 publications
1
72
1
11
Order By: Relevance
“…Cultural epidemiological studies have been particularly useful in examining the link between the distribution of socio-cultural features of illness and designated outcomes of importance for disease control and public health for infectious and chronic illnesses. [19][20][21][22] This study was performed in Zanzibar within a project managed by the WHO. The project's main objective was to vaccinate community residents in selected cholera hotspots on both islands of Zanzibar to assess the effectiveness of OCV under real-life conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Cultural epidemiological studies have been particularly useful in examining the link between the distribution of socio-cultural features of illness and designated outcomes of importance for disease control and public health for infectious and chronic illnesses. [19][20][21][22] This study was performed in Zanzibar within a project managed by the WHO. The project's main objective was to vaccinate community residents in selected cholera hotspots on both islands of Zanzibar to assess the effectiveness of OCV under real-life conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Other researchers who explored these cultural characteristics as they relate to tuberculosis and cancer have found similar results (Coreil et al, 2010;Gany, Herrera, Avallone, & Changrani, 2006). One study found that being Haitian was related to higher rates of refusal of routine HIV testing at urgent care centers (Liddicoat, Losina, Minhee, Freedberg, & Walensky, 2006).…”
Section: Literature Reviewmentioning
confidence: 58%
“…37,38 Some argue that TB stigma is hard to distinguish from xenophobia, elitism and racism. 9,39 Other researchers suggest it is so bound up with HIV stigma that trying to tease them apart may be a fool's errand. 13,[40][41][42] Specific drivers may depend on the type of stigma, setting, population and type of TB.…”
Section: Resultsmentioning
confidence: 99%